GaN LEDs with in situ synthesized transparent graphene heat-spreading electrodes fabricated by PECVD and penetration etching. Issue 17 (11th April 2022) - Xiong, Fangzhu; Sun, Jie; Cole, Matthew T.; Guo, Weiling; Yan, Chunli; Dong, Yibo; Wang, Le; Du, Zaifa; Feng, Shiwei; Li, Xuan; Guo, Tailiang; Yan, Qun
Abstract : High-quality and patterned graphene is grown directly on GaN LED arrays for transparent and heat-spreading electrodes. The CVD is done at 600 °C for 2 min. Sacrificial Co acts both as GaN mesa etching mask and transfer-free graphene growth catalyst. Abstract : Currently, applying graphene on GaN based electronic devices requires the troublesome, manual, lengthy, and irreproducible graphene transfer procedures, making it infeasible for real applications. Here, a semiconductor industry compatible technique for the in situ growth of patterned graphene directly onto GaN LED epiwafers for transparent heat-spreading electrode application is introduced. Pre-patterned sacrificial Co acts as both an etching mask for the GaN mesa and a catalyst for graphene growth. The Co helps in catalyzing the hydrocarbon decomposition and the subsequent graphitization, and is removed by wet etching afterwards. The use of plasma enhancement in the graphene chemical vapor deposition reduces the growth temperature to as low as 600 °C and improves the graphene quality, where highly crystalline graphene can be obtained in just 2 min of deposition. This method reduces the exposure of the GaN epilayers to high temperature to its limit, avoiding the well-known GaN decomposition and In segregation problems. Importantly, it can directly pattern the graphene without using additional lithographic steps and in doing so avoids any unintentional deleterious doping and damage of graphene from contact with the photoresist. The approach simplifies the fabrication and enables mass production by eliminating the bottlenecks of graphene transfer and patterning procedures. By comparing the GaN LEDs with and without graphene, we find that graphene greatly improves the device optical, electrical and thermal performances, due to the high optical transparency (91.74%) and high heat spreading capability of the graphene electrode. Unlike transferred graphene, this method is intrinsically scalable, reproducible, and compatible with the planar process, and is beneficial to the industrialization of GaN-graphene optoelectronic devices, where the integrated graphene serves as a superior sustainable and functional substitute to other transparent conducting materials such as ITO.